Proceedings of the 7th International Conference on Collaborative Computing: Networking, Applications and Worksharing 2011
DOI: 10.4108/icst.collaboratecom.2011.247115
|View full text |Cite
|
Sign up to set email alerts
|

ChameleonSoft: A Moving Target Defense System

Abstract: Ubiquitous cyber systems and their supporting infrastructure impact productivity and quality of life immensely. Their penetration in our daily life increases the need for their enhanced resilience and for means to secure and protect them. One major threat is the software monoculture. Latest research work illustrated the danger of software monoculture and introduced diversity to reduce the attack surface. In this paper, we propose a biologically-inspired defense system, ChameleonSoft, that employs multidimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…It maximizes the unpredictability by solving the optimal graph-coloring problem. Azab et al [91] proposed bionics-based software diversification for complex applications. It segments complex software into smaller tasks.…”
Section: Single-layer Mtdmentioning
confidence: 99%
“…It maximizes the unpredictability by solving the optimal graph-coloring problem. Azab et al [91] proposed bionics-based software diversification for complex applications. It segments complex software into smaller tasks.…”
Section: Single-layer Mtdmentioning
confidence: 99%
“…To be more effective and practical, an MTD system should also be equipped with the reactive ability, which responds to an anomalous event observed or perceived (Carvalho et al, 2012). Currently, some existing mechanisms have been designed with active and reactive abilities simultaneously, such as ChameleonSoft (Azab et al, 2011) and moving attack surface (MAS) (Huang and Ghosh, 2011). In other words, the operation mode of MTDs is no longer consistent with the traditional PPDRR security model; i.e., the introduction of MTD changes the general defense process of traditional defense mechanisms and approaches, and produces a new security model accordingly.…”
Section: Recoverymentioning
confidence: 99%
“…Selection means choosing a new parameter with its value or assigning a new value to the previous moving parameter(s) from its(their) domain(s) through various ways, such as choosing randomly (Roeder and Schneider, 2010;Azab et al, 2011;Jafarian et al, 2012), choosing according to the game theory (Manadhata, 2013; Zhu and Başar, 2013;Carter et al, 2014), and choosing according to the attack behavior observed or the situation of cyber-security (Azab et al, 2011;Huang and Ghosh, 2011;Jia et al, 2013). Replacement is using the selected new parameter with its value or the selected new value to replace the old one.…”
Section: Moving Target Defense Theorymentioning
confidence: 99%
See 2 more Smart Citations